Nexus between Effective Payment Methods, Low Distribution Charges, Low Transit Time and Online Brand Loyalty: Moderating Role of Effective Management - Erum Fayyaz; Muhammad Murad; Yaqub, Shahid; Muhammad Naeem Sharif (Pakistan Journal of Humanities and Social Sciences, 2022)
The online brands in Pakistan are facing brand loyalty issues as the market is new and emerging for Pakistani consumers. The less satisfaction of consumers with different operations of online businesses is the fundamental reason for this loyalty challenge. The purpose of this study is to identify different factors that are contributing to the brand loyalty of online businesses in Pakistan. The Likert scale questionnaire was used to collect data from the Pakistani people with a random sampling technique. The Partial Least Square (PLS) method is used to test the relationship between different variables of the study. The study highlights that effective payment method, low distribution charges and low transit time has key responsibility for brand loyalty of the Pakistani customers with moderating role of effective management. The study is a contribution to literature and knowledge as the framework of the study contains significant variables. The practical implications of this study would provide a way for online businesses in Pakistan to develop brand loyalty.